Analisis Kepadatan bakteri Coliform serta hubungannya dengan konsentrasi Nitrat dan Fosfat di Pantai wisata Hamadi, Kota Jayapura. - Popi Ida Laila Ayer; Vera Kosntansie Mandey (Cenderawasih University, 2022)
There are several kinds of tourist objects in Jayapura City, one of which is the Hamadi beach tourist attraction. Tourists on Hamadi beach increases anthropogenic activities which can cause the aesthetics of the waters to decrease. Physical and chemical pollution can increase biological pollution, namely the presence of pathogenic bacteria such as coliform bacteria. Tourist beach waters that have been contaminated with Coliform bacteria will have an impact on tourists. The conducted of this study was to determine the density of Coliform bacteria, Nitrate and Phosphate concentrations and the relationship between Coliform bacteria density and Nitrate and Phosphate concentrations. The method used in this study was a survey method with a quantitative descriptive approach, while the data collection technique used a purposive random sampling technique at 3 stations with 3 points at each station. Data analysis used includes analysis of Coliform bacteria density, analysis of water quality based on the quality standard of the relationship between coliform bacteria density and concentrations of nitrate and phosphate using Pearson correlation analysis. The results showed that the average density of bacteria at station I was found to be 494 colonies/100mL, station II was found to be 58 colonies/100mL and station III was found to be 35 colonies/100mL. Nitrate and Phosphate concentrations in the coastal waters of Hamadi tourism were at station I the concentration of nitrate 1.90 mg/L and phosphate 0.045/mg/L. The concentration of nitrate at Station II was 2.4 mg/L and phosphate, which was 0.41, exceeded the water quality standard (0.015). Nitrate and phosphate concentrations at Station III were 4.40 mg/L nitrate and 0.060/mg/L phosphate. Based on the Pearson correlation test, the relationship between the density of Coliform bacteria and the concentration of Nitrate and Phosphate in the waters of the Hamadi tourism beach was found to have an opposite or weak and moderate relationship.